Pengaruh Psychological Capital dan Job Enjoyment terhadap Intensi Job Hopping pada Karyawan Generasi Y - Sulik Kusuma Putri (CV. Syntax Corporation Indonesia, 2021)
This study was conducted to empirically examine the role of psychological capital and job enjoyment in explaining the job hopping intentions of the Indonesian millennial generation. Job hopping intention in this study refers to the tendency of employees to change jobs voluntarily even though their tenure is less than 2 years (YUEN, 2016). From the data collected, 165 subjects were employees of Generation Y and filled out a questionnaire distributed online. The employees involved are permanent employees who have worked for less than two years. The method used in this study is the Psychological Capital Questionnaire (PCQ), which is structured in four dimensions (Luthans et al., 2007). Job enjoyment is measured by The ENJOY Scale which is composed of five dimensions (Davidson, 2018). In addition, this study also uses the Job Hopping Intent (JHI) scale developed by (YUEN, 2016). SPSS Statistics 22.0 for Windows application is used to determine the significant effect of the two independent variables. The results of this study indicate that psychological capital (R2 = 0.085) and job enjoyment (R2 = 0.052) have a negative effect on job hopping intentions when the two independent variables are analyzed separately. When studied simultaneously, the two independent variables affect job hopping intentions (R2 = 0.086), but the job enjoyment variable partially has a limited effect (ΔR2 = 0.001). This study also performed a simple regression analysis on psychological capital and job enjoyment variables. Three of the four dimensions of psychological capital (optimism, hope and resilience) affect job hopping intentions, while the self-efficacy dimension has no effect. Second, four of the five dimensions of job enjoyment (pleasure, relatedness, competence, and challenge/improvement) also affect job hopping intentions, but not on the engagement dimension.